Perkembangan Transaksi Ekonomi Digital di Indonesia - Raihan Zuhri; Rangkuty, Dewi Mahrani; Wahyu Indah Sari; Nasution, Lia Nazliana; Bakhtiar Efendi; Rusiadi (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
The digital economy in Indonesia has both positive and negative impacts on the country's development. The development of the digital economy allows the government or society to become a platform for carrying out various types of economic transactions. This research was designed to analyze the development of the digital economy and the behavior of social media users in economic transactions. .In this research, descriptive analysis method was used using literature study. The development of the digital economy in Indonesia not only encourages economic growth, but also changes the way people interact and make transactions. Challenges such as uneven infrastructure and the need for clear regulations still need to be overcome to maximize this potential. The fintech sector is growing rapidly with many companies providing digital payment services, online loans and investments. OJK (Financial Services Authority) is also active in regulating this sector.